senderización y señalética para la estación de El Padmi, parroquia Los Encuentros, cantón Yanzatza, Provincia de Zamora Chinchipe - Alvarado Nole, Ketty Marilú (2016)
The local tourism development progress are strategies that are based on the territorial potential of natural and social wealth of a community. In recent years it seeks to project the development of tourism through the preservation of the environment, in addition to working with the community that the practice of community tourism. From this perspective, the present study aims to contribute to local tourism development by proposing "SENDERIZACIÓN AND SIGNAGE FOR SEASON THE PADMI, PARISH MEETINGS, YANTZAZA CANTON, PROVINCE OF ZAMORA CHINCHIPE" with which it seeks to collaborate with the conservation and protection of flora and fauna in the station by supplementing with the implementation of trails and signage, allowing these areas to be traversed by tourists being the ones who contribute to the preservation of natural resources. The specific objectives in this work are the next: "Making the tourist diagnosis Station The Padmi Parish Los Encuentros Yantzaza Canton, Province of Zamora Chinchipe"; "Propose senderización and signage for The Station Padmi Parish Los Encuentros, Canton Yantzaza, Zamora Chinchipe" and "Socialize the proposal with you stakeholders". As for the results of this research and based on the objectives it is mentioned that the diagnosis was made at The Station Padmi, well Parish The meetings closest to where the study population were analyzed aspects like basic infrastructure services, transport, governance, etc. With fieldwork georeferencing attractions Station was performed, the geographical coordinates of the attractions identified were taken, then all data is entered the geographic information system (GIS) and established a satellite map with the location attractions, scenic beauty leverage existing 5 at the site, the area to be used to implement the signage and the two paths in which stand out for having the largest number of natural attractions were determined was established. For the first objective results of analytical and synthetic methods were used for the diagnosis Ricaurte Carla matrix was used, tokens Ministry of Tourism information lies in the Municipal and Parish GAD, and direct observation techniques and interview with Ing. Oswaldo Guaya Station manager The Padmi. For the proposal and signage senderización inductive and deductive methods, use of GPS, the capacity of Miguel Cifuentes and Signage Manual 2011 Ministry of Tourism and used to complete the socialization was conducted with the use of the technique of MARPP (participatory workshop) that included three phases: Previous, execution and Conclusions and Recommendations. Among the conclusions we have senderización and lack of signage has not allowed to know the station's Padmi; It is important to the development of this place and make the community participatory projects that improve their quality of life; It has several attractions and activities to be undertaken but the lack of dissemination and the lack of interest given to this place, has not allowed students to know both of our alma mater worse visited by tourists. With regard to the recommendations are addressed to the authorities of the National University of Loja, in order to make this a useful space for all university students whatever their career, has many activities to be developed as one of the most important tourism suggesting that students do their pre-professional in this Research Station.